Pola Keruntuhan Jembatan Rangka Menerus Tipe Waren - Heri Istiono; Eka Susanti (Jurusan Teknik Sipil, Fakultas Teknik, Universitas Borneo Tarakan, 2019)
Bridge damage often occurs, as a result of damage to the bridge causing financial aspects losses and can also cause fatalities. The causes of the damage various factor, one of which is the bridge structure experiencing fatigue. This fatigue caused the strength of the structure of the bridge to decrease. Bridge damage due to a decrease in the strength of this bridge structure can impact the bridge to collapse. To minimize bridge damage due to a decrease in the strength of the structure of the bridge there is a need for bridge maintenance and to make it easier in terms of maintenance it is necessary to know the pattern of collapse of the existing bridge. In the analysis of this collapse pattern, a waren type steel continous bridge will be modeled with a span length of 120 meters. This analysis is carried out by giving a static vertical load at a reference point on the bridge frame, where the load is increased by multiplying until the structure is demage. The results of the study show that in the waren type continuous steel truss bridge failure occurs at the final portal diagonal element in the 2 middle positions. Based on FEMA 356 displacement target, the level of structural performance shows the bridge model under IO conditions and based on SNI 2833-2008, the actual ductility that occurs has met the requirements.